2004
DOI: 10.1177/019263650408864102
|View full text |Cite
|
Sign up to set email alerts
|

Catching Up: Effect of theTalent Development Ninth-Grade Instructional Interventions in Reading and Mathematics in High-Poverty High Schools

Abstract: Little is known about the feasibility and rapidity with which the academic learning of students who enter high school multiple years behind grade level can be accelerated. This study uses multiple regression analyses of standardized test and survey data from high-poverty high schools in two large urban districts to evaluate initial effects of the Talent Development High Schools (TDHS) ninthgrade instructional program in reading and mathematics. Pre-, post-, and match-control comparisons show that students in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…Nevertheless, these findings have been used to suggest that all students should have the opportunity to enroll in algebra (Balfanz et al, 2004;Everson & Dunham, 1996). Studies summarized in Part 2 demonstrate that, under "selection" conditions, taking algebra does indeed predict taking more advanced mathematics courses in high school and earning higher mathematics achievement scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, these findings have been used to suggest that all students should have the opportunity to enroll in algebra (Balfanz et al, 2004;Everson & Dunham, 1996). Studies summarized in Part 2 demonstrate that, under "selection" conditions, taking algebra does indeed predict taking more advanced mathematics courses in high school and earning higher mathematics achievement scores.…”
Section: Discussionmentioning
confidence: 99%
“…The concern over inequitable selection processes has been part of the impetus for state and district policies mandating algebra for all eighth or ninth graders (Balfanz, Legters, & Jordan, 2004;Everson & Dunham, 1996). This is likely the result of higher enrollments within schools, but also more schools are offering algebra in eighth grade.…”
Section: Summary: Us Trends For Who Is Taking Algebra and Whenmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not surprising that several mathematics education researchers confirmed that providing a cooperative learning environment in which teachers engage students in group projects and connect their academic work to everyday life experiences/examples is crucial to successful mathematic learning experiences of minority and/or working class students (Boaler, 2006;Balfanz, Legters, & Jordan, 2004). Mrs. Oliver's traditional math classroom failed to foster such connection among different groups of students as well as between her and those coming from other than white middle class families.…”
Section: Discussionmentioning
confidence: 99%
“…While acknowledging the compounding impact of class and race, researchers found that some mathematics teaching strategies reflecting black, working-class students' cultural and learning dispositions were more effective. They reported that providing a cooperative learning environment in which teachers engage students in group projects and connect their academic work to everyday life experiences/examples is crucial to successful mathematic learning experiences of low SES minority students (Balfanz, Legters, & Jordan, 2004;Boaler, 2006).…”
Section: Double Jeopardy: Class and Race In Poor Minority Girls' Mathmentioning
confidence: 99%